Salinity-induced cytosolic alkaline shifts in Arabidopsis roots require the SOS pathway - Rombolá Caldentey, Maria Belén; Andrés González, Zaida; Waadt, Rainer; Quintero, Francisco J.; Schumacher, Karin; Pardo, José M. (International journal of molecular sciences, 2023)
Plants have evolved elaborate mechanisms to sense, respond to and overcome the detrimental effects of high soil salinity. The role of calcium transients in salinity stress signaling is well established, but the physiological significance of concurrent salinity-induced changes in cytosolic pH remains largely undefined. Here, we analyzed the response of Arabidopsis roots expressing the genetically encoded ratiometric pH-sensor pHGFP fused to marker proteins for the recruitment of the sensor to the cytosolic side of the tonoplast (pHGFP-VTI11) and the plasma membrane (pHGFP-LTI6b). Salinity elicited a rapid alkalinization of cytosolic pH (pHcyt) in the meristematic and elongation zone of wild-type roots. The pH-shift near the plasma membrane preceded that at the tonoplast. In pH-maps transversal to the root axis, the epidermis and cortex had cells with a more alkaline pHcyt relative to cells in the stele in control conditions. Conversely, seedlings treated with 100 mM NaCl exhibited an increased pHcyt in cells of the vasculature relative to the external layers of the root, and this response occurred in both reporter lines. These pHcyt changes were substantially reduced in mutant roots lacking a functional SOS3/CBL4 protein, suggesting that the operation of the SOS pathway mediated the dynamics of pHcyt in response to salinity.